KONSTRUKSI ILMU MANTIQ PERSPEKTIF FILSAFAT ILMU - Muhammad Mushlih (CV. ALIM'SPUBLISHING, 2025)
The science of Mantiq (logic) has a very important role in the development of science, especially in helping the structure and validity of scientific reasoning. Mantiq's construction of science from a philosophy of science perspective combines the studies of epistemology, axiology, and ontology to understand how logistics knowledge is built and applied in various scientific disciplines. This research aims to explore the role of Mantiq in the formation of valid knowledge, as well as exploring the relationship between logical principles and theories in the philosophy of science. The aim of this research is to provide a deeper understanding of Mantiq science in building valid and rational knowledge and how logic can be applied in a broader scientific context from a philosophy of science perspective. The method used in this research is a literature study (library study). The research results show that Mantiq science has a central role in formulating coherent and accountable knowledge, as well as revealing the challenges that arise in its application in contemporary science. Apart from that, Mantiq's science construction also highlights the importance of integrating logic with ethical values ​​and a deep understanding of reality to produce more accurate and applicable knowledge.